Formulating finger millet (eleusine coracana l.) and cowpea (vigna unguiculata) food blend for enhanced micronutrients for children below 5 years - Chinyama, J.; Masamha, B.; Nyamadzawo, G. (African Scholarly Science Communications Trust (ASSCAT), 2023)
Malnutrition of children under 5 years is a public health concern because it is the most vulnerable stage of child’s growth where its impact results in long term health conditions such as stunting, wasting, obesity and poor cognitive development. This study aimed at developing a Rapoko-Cowpea porridge blend to enhance dietary micronutrients among children below the age of 5 years and assess its sensory acceptability. A mixed methods research approach was adopted consisting of a quasi- experiment and a cross sectional survey. Vendors from Mbare market were clustered based on the source of their finger millet and cowpea grains (Masvingo, Murewa, Gokwe). A Completely Randomised Design (CRD) was used with three treatments (blends) replicated three times. Proximate analysis was done using standard AOAC methods. Compared to cowpea, finger millet had the highest levels of carbohydrates (78.12g/100g), iron (8.7mg/100g), zinc (3.77mg/100g). Results also show that 75:25. Rapoko-Cowpea blend ratio had the ability to meet WHO daily nutrient requirements for children under the age of 5 years. Blend ratio of Rapoko: cowpeas (75:25) had the highest carbohydrates (69.41g/100g), protein (25.64g/100g), zinc (1.74mg/100g), iron (5.14mg/100g), energy (411.37kcal), and vitamins (0.11 mcg RAE) with RaCoB1 blend having the lowest nutrient composition. Results have showed that finger millet (Rapoko), cowpeas and RaCoB (Rapoko-Cowpea blend) blends have high macro and micronutrients (iron and zinc) to support daily nutritional requirements of children below the age of 5 years and may help in addressing malnutrition. Sensory evaluation was done with 100 panellists from the University of Zimbabwe and of the three blends, a 75:25 ratio was the most preferred (90.88%). Further studies need to analyse the effects of anti-nutritional factors, bioavailability of nutrients, shelf life of the food blend and commercialization potential of RaCoB blends. The government is therefore encouraged to provide agronomic support for increased productivity of small grains and pulses through improved research and extension. There is a need to develop a policy at national level that promotes blending of cereals and pulses as well as innovative small scale food processing initiatives through private-public partnerships. Keywords: Children under 5 years, Cowpea, food blending, Malnutrition, Micronutrients, Rapoko, Sensory evaluation
Keywords: Food blending; Malnutrition; Food micronutrients